Clinical researchEffect of N-acetylcysteine on microalbuminuria in patients with acute respiratory distress syndrome - Najafi, Atabak; Mojtahedzadeh, Mojtaba; Mahmoodpoor, Ata; Aghamohammadi, Mostafa; Ahmadi, Arezou; Nahreini, Sheida; Pazuki, Marzieh; Reza Khajavi, Mohammad; Abdollahi, Mohammad (Archives of Medical Science, 2009)
Introduction: Acute respiratory distress syndrome (ARDS) is associated with enlarged permeability of respiratory capillaries resulting in interstitial edema and microalbuminuria. This study investigated the effect of early treatment with N-acetylcysteine (NAC) on microalbuminuria/creatinine ratio and clinical improvement in ARDS. Material and methods: Twenty-three patients with ARDS were randomly entered into two groups of study including regular therapy and regular therapy plus NAC. NAC was started with 150 mg/kg on the first day followed by 50 mg/kg at the second day. Urine sample was tested for microalbuminuria on 4, 6, 12, 24, 36, and 48 h post baseline. Results: No significant correlation was found between microalbumin/creatinine ratio (MACR) and acute physiology and chronic health evaluation (APACHE II) or PaO2/FiO2 ratio and blood pressure in each group. Non-survivors showed higher urine albumin creatinine ratio (ACR) and physiologic scores than survivors. The patients outcome who treated with NAC showed significant improvement comparing with controls. Conclusions: NAC improves global hypoxemia in the patients with acute lung injury. Improvement of oxidant/antioxidant balance by NAC increases the survival of patients with ARDS who are under oxidative crisis. Although limitations of this study do not let us to reach a conclusive decision but the impact of microalbominuria as a predictive of survival in ARDS patients receiving NAC seems essential. Conducting larger clinical trials are recommended.